ANALISIS MOTIVASI BELAJAR SISWA KELAS V SEKOLAH DASAR SEGUGUS 1 KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Ika Nurrahmah; Syahrilfuddin Syahrilfuddin; Zufriady Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated as long as the researchers carry out practical teaching activities in the field (PPL) in one of the elementary schools in Pekanbaru, namely SD Muhammadiyah 6 Pekanbaru, especially in the practice class, which is the VA class of 24 students, almost as much as 55% of students in the class according to the observations of the researchers. very low and it is caused by the ability they have that has disrupted the learning process. This study aims to find out and analyze what are the indicators that influence student motivation in grade V in elementary school in the cluster 1 Payung Sekaki district, Pekanbaru. This type of research uses descriptive quantitative methods, the instrument used in this study uses a questionnaire (questionnaire). The population in this study was grade V students, amounting to 255 students with a sample of 72 students. Data collection was carried out using a questionnaire, based on the results of the processed data obtained 85,654% influenced by the goal, 82,078% influenced by changes in energy, 81,272% influenced by feeling / feeling. The conclusion of this study according to the results of the acquisition of the percentage of indicators that most influence on student motivation is the goal indicator with 85.654%. The more valuable the goal is for the individual the stronger the motivation. Key Words: Analysis, Motivation and Learning